2007
DOI: 10.1038/sj.ijo.0803573
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year trends in health-related quality of life after surgical and conventional treatment for severe obesity: the SOS intervention study

Abstract: Objective: To examine trends and effects of weight loss treatment on health-related quality of life (HRQL) in the severely obese over 10 years. Design: Swedish obese subjects (SOS) intervention study is a controlled, longitudinal trial of the health effects of weight loss in the severely obese. Subjects: A total of 655 of 851 surgically treated and 621 of 852 conventionally treated obese men (body mass index, BMIX34) and women (BMIX38) who completed 10 years of the study. Measurements: HRQL was assessed before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
532
6
39

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 733 publications
(636 citation statements)
references
References 53 publications
48
532
6
39
Order By: Relevance
“…Previous systematic reviews reporting on quality of life (QoL) as a main or secondary outcome, concluded that although BS improves short term (two years) health-related quality of life (HRQoL) in obese adults, longer term (ten years) effects were less clear [39] with some measures showing significantly greater change after surgery, but not others. However, not all the studies included in the systematic reviews assessed QoL and outcome data for QoL was unclear for almost half of the studies reviewed, thus making it difficult to make clear judgements about the impact of weight loss interventions on longer term quality of life [18 & 19].…”
Section: Why Is It Important To Do This Review?mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous systematic reviews reporting on quality of life (QoL) as a main or secondary outcome, concluded that although BS improves short term (two years) health-related quality of life (HRQoL) in obese adults, longer term (ten years) effects were less clear [39] with some measures showing significantly greater change after surgery, but not others. However, not all the studies included in the systematic reviews assessed QoL and outcome data for QoL was unclear for almost half of the studies reviewed, thus making it difficult to make clear judgements about the impact of weight loss interventions on longer term quality of life [18 & 19].…”
Section: Why Is It Important To Do This Review?mentioning
confidence: 99%
“…The most commonly cited co-morbidities were diabetes and cardiovascular disease. The individual study sample size ranged from 43 to 1276 [52,39]. The majority of participants in the studies were female and mean age ranged from 39 years [55] to 48 years [39] which is representative of the BS population in the UK [14] Group differences in baseline characteristics were noted in most of the studies apart from the four controlled trials [51,52,56,39] and Buddeberg-Fischer et al [54].…”
Section: Representativenessmentioning
confidence: 99%
See 3 more Smart Citations